PERANAN SIKAP MAHASISWA TERHADAP GAYA KEPEMIMPINAN DIREKTUR AKADEMI MANAJEMEN BUMI SEBALO BENGKAYANG - Tri Purwani (Jurnal Ekonomi Integra, 2019)
The purpose of this study was to determine student attitudes toward the leadership style of the Sebalo Bengkayang Academy of Management. The research variables consist of attitude and leadership style. The population is all active students of the Sebalo Bengkayang Earth Management Academy. The sample was represented by 114 students taken using the Slovin formula randomly drawn. The research instrument used a closed question type questionnaire. Indicators are arranged in a construct based on the theme. Hypothesis testing using behavioral models from Fishbein and Ajzen. The results of the study concluded that the attitude of students included in the category is quite good, according to the findings it can be stated that Ha is accepted and H0 is rejected, significantly that students have a positive attitude towards leadership style